2018
DOI: 10.3390/infrastructures3020008
|View full text |Cite
|
Sign up to set email alerts
|

Novelties in Material Development for Massive Concrete Structures: Reduction in Heat of Hydration Observed in Ternary Replacement Mixtures

Abstract: As the size of modern infrastructure increases, novelties related to mass concrete mixtures including supplementary cementitious materials (SCMs) become critical. The effects of binary and ternary cement replacement mixtures including metakaolin, silica fume, ground calcium carbonate, granulated blast furnace slag, and fly ash on the rate and amount of heat generated in concrete mixtures are investigated. Twenty three binary and ternary mixtures with a water-to-cementitious binder ratio of 0.43 are evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
(102 reference statements)
1
7
0
Order By: Relevance
“…A time history of the CTEs should be studied if ternary mixtures are to be used in mass concrete placements. A previous study [9] has reported the reduced heat of hydration in these ternary mixtures. The relationship between CTE and the extent of temperature-induced cracking should be of future interest.…”
Section: Future Workmentioning
confidence: 83%
See 4 more Smart Citations
“…A time history of the CTEs should be studied if ternary mixtures are to be used in mass concrete placements. A previous study [9] has reported the reduced heat of hydration in these ternary mixtures. The relationship between CTE and the extent of temperature-induced cracking should be of future interest.…”
Section: Future Workmentioning
confidence: 83%
“…To control the dilution effect, ternary SCM combinations shall also replace a portion of cement equaling 45%. Literature indicates that the heat of hydration is minimized at a 45% replacement when replacements by metakaolin and slag are 15% and 30% of the cement content, respectively [9]. Therefore, all combinations of metakaolin and slag in this study shall be 15% and 30% of the cement content, respectively.…”
Section: Materials and Experimental Planmentioning
confidence: 97%
See 3 more Smart Citations